Efficacy and Safety of Intensity-Modulated Radiotherapy Following Transarterial Chemoembolization in Patients With Unresectable Hepatocellular Carcinoma. Issue 21 (May 2016) - Zhang, Tao; Zhao, Yu-Ting; Wang, Zhi; Li, Cheng-Rui; Jin, Jing; Jia, Angela Y.; Wang, Shu-Lian; Song, Yong-Wen; Liu, Yue-Ping; Ren, Hua; Fang, Hui; Bao, Hui; et al.
Abstract : Abstract: Three-dimensional conformal radiotherapy in combination with transarterial chemoembolization (TACE) has been beneficial in patients with unresectable hepatocellular carcinoma (HCC). There have been few clinical reports on the use of intensity-modulated radiotherapy (IMRT) in combination with TACE for these patients. The purpose of this study was to assess the efficacy and toxicity of IMRT following TACE in unresectable HCC. The medical records of consecutive patients with unresectable HCC, who underwent IMRT following TACE from January 2009 to June 2014, were retrospectively reviewed in order to assess the overall survival (OS), progression-free survival (PFS), tumor response, and treatment-associated toxicity. A total of 64 lesions in 54 patients were included in the analysis. IMRT was delivered at a median dose of 50 Gy (range 44–70 Gy) at 1.8 to 2.0 Gy per fraction. The overall response rate was achieved in 64.8% of patients with complete response in 20.4% of patients at 3 months after completion of IMRT. The median OS was 20.2 months (95% CI = 8.6–31.9), and the actuarial 1-, 2-, and 3-year OS rates were 84.6%, 49.7%, and 36.7%, respectively. The median PFS was 10.5 months (95% CI = 7.3–13.7) and the 1-, 2-, and 3-year PFS rates were 44.2%, 23.4%, and 14.6%, respectively. The responders had a significantly higher OS rate than the nonresponders (3-year OS 48.0% vs 14.4%, P  = 0.001). During and the first month following IMRT, 10 (18.5%) patients developed grade 3 hematological toxicity, and 3 (5.6%) developed grade 3 hepatic toxicity. No patient experienced grade 4 or 5 toxicity. Radiation-induced liver disease was not observed. Our findings suggest that IMRT following TACE could be a favorable treatment option for both its safety profile and clinical benefit in patients with unresectable HCC.